1994
DOI: 10.3801/iafss.fss.4-205
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Environment Prediction In Steel-bounded Preflashover Compartment Fires

Abstract: Fifteen natural ventilation and twelve forced ventilation compartment fire experiments were conducted in a steel ship wmpartment. Experimental results were used to modify a temperature correlation, developed by Deal and Beyler [I], making it applicable to compartments with conductive boundaries. In addition to validating the temperature correlation using measured vent flow rates, the use of predicted vent flow rates was investigated. The McCaffrey, Quintiere, and Harkleroad (MQH) Method for temperature predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The expression for the effective heat transfer coefficient by Peatross and Beyler [4] improved, however, the results for the non-insulated case considerably.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The expression for the effective heat transfer coefficient by Peatross and Beyler [4] improved, however, the results for the non-insulated case considerably.…”
Section: Discussionmentioning
confidence: 94%
“…The fire temperature predictions differed the most, about 30 K. In the second half of the test FDS gave under predictions of 20-60 K. The original MQH relationship gave again unrealistic results. However, the modified relationship with a corrected heat transfer coefficient as suggested by Peatross and Beyler [4] predicted the experiments well.…”
Section: Fire Temperature Comparisonmentioning
confidence: 87%
See 1 more Smart Citation
“…As pool fires in ventilation restricted compartments burn at steady state, with a constant air entrainment, the present work was carried out at a fixed ventilation rate with the compartment air flow externally controlled to give 10.6 ACH, which is equivalence to a closed door with high air leakage. The lowest value of K in that has been studied prior to this work was 1.32% in the work of Sugawa et al [11], 1.7% by Peatross and Beyler [12] and 1.9% by Audouin et al [13]. All of these investigators used pool fires as the fire load and all found ghosting flames occurred.…”
Section: Introductionmentioning
confidence: 94%
“…For enclosures with thermally thin boundaries (eg. steel), Peatross and Beyler [17] determined that the correlation developed Deal and Beyler [16] can be used with a modified heat transfer coefficient to quantify the heat losses to the wall. Therefore, for thermally thin boundaries Eqn.…”
Section: Effects Of Hot Gas Layersmentioning
confidence: 99%